2018
DOI: 10.1590/s0100-204x2018000700007
|View full text |Cite
|
Sign up to set email alerts
|

Occasional soil tillage, liming, and nitrogen fertilization on long-term no-tillage system

Abstract: The objective of this work was to evaluate the residual effects of occasional soil tillage in a 17-year-old, no-tillage system, associated with liming and nitrogen fertilization, on the crop yields and chemical properties of a very clayey Oxisol in the South of Brazil. A randomized complete block design in split-split plots was used, with two soil managements (with or without plowing), two liming treatments (with or without the required dose to raise base saturation to 70%), five N doses applied on side-dress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…Accordingly, CA in combination with fertilization (fertilized = 5.92 and unfertilized = 5.95) increased pH levels compared to CT in combination with fertilization (fertilized = 5.46 and unfertilized = 5.44). These findings agree with other studies [29], namely a significant influence by the tillage system in combination with N fertilization on pH, where higher values were recorded under CA than CT.…”
Section: Competitive Ratio (Cr)supporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, CA in combination with fertilization (fertilized = 5.92 and unfertilized = 5.95) increased pH levels compared to CT in combination with fertilization (fertilized = 5.46 and unfertilized = 5.44). These findings agree with other studies [29], namely a significant influence by the tillage system in combination with N fertilization on pH, where higher values were recorded under CA than CT.…”
Section: Competitive Ratio (Cr)supporting
confidence: 93%
“…The findings corroborate with those of other investigators [31,32], who reported a significant influence on OC by the interaction of the tillage system and N fertilization. A decrease in organic matter under CT and N fertilization interaction was also reported [29].…”
Section: Organic Carbonsupporting
confidence: 57%
“…The improved nutrient use efficiency of nextgeneration fertilizers has been linked to several mechanisms that can enhance crop yield and quality. For example, a controlled release of nutrients can provide plants with a consistent supply of essential elements, resulting in better photosynthesis, stress tolerance, and overall growth [13,14]. This consistent supply can also reduce the risk of nutrient deficiencies or toxicities that could limit crop development and yield potential.…”
Section: Mechanisms Of Action In Enhancing Crop Yield and Qualitymentioning
confidence: 99%
“…For instance, an adequate supply of nitrogen (N) from controlledrelease or stabilized fertilizers can improve protein synthesis and grain protein content, leading to higher nutritional quality [6]. Additionally, a more efficient uptake of nutrients can also promote the accumulation of desirable compounds, such as antioxidants and vitamins, further enhancing the quality of maize grains [14].…”
Section: Mechanisms Of Action In Enhancing Crop Yield and Qualitymentioning
confidence: 99%
See 1 more Smart Citation